Gambaran Edukasi Memilah Sampah Dalam Upaya Menanamkan Kepedulian Lingkungan Di KB Agung Kencana - Khusniyah, Mufidatul; Wijayanti, Rina; Muntomimah, Siti (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the level of effectiveness of this waste sorting program in instilling the character of environmental care, introducing children to the problems that occur in the environment around children, what are the impacts of waste, introducing the types of waste, so that children are able to distinguish between organic and non-organic waste and know what can be utilized from non-organic and organic waste, as well as knowing the inhibiting and supporting factors of this program. The research method here uses descriptive qualitative methods to explore the impact of the socialization of sorting this waste on early childhood totaling 34 at KB Agung Kencana. This research is expected to provide an understanding of the impact of environmental damage due to waste, how to separate waste according to its type, and its management. In addition, children are also given direct experience in the process of sorting and managing waste and cleaning the surrounding environment. As a result of this research, the socialization of sorting waste is one of the teacher's efforts to instill the character of environmental care in early childhood. So that students will have an environmental care character that plays an important role in preserving the environment. This activity not only provides an understanding of the adverse effects of waste and how to separate it by type, but also provides direct experience in the process of sorting and managing waste and maintaining environmental cleanliness. In its implementation, the supporting factor is the commitment and support of parents in the waste sorting process, while the inhibiting factor is the limited facilities and infrastructure for waste management.